Vestibular Migraine in an Otolaryngology Clinic. Issue 1 (January 2015) - Van Ombergen, Angelique; Van Rompaey, Vincent; Van de Heyning, Paul; Wuyts, Floris
<x xml:space="preserve">Abstract</x> Objective To assess the prevalence of vestibular migraine (VM) in patients consulting to an otolaryngology clinic, the neuro-otological associated symptoms, and the effect of prophylactic antimigrainous medication on VM symptom improvement. Study Design Retrospective chart review. Setting Tertiary referral otolaryngology clinic. Subjects and Methods We used the diagnostic criteria from the Bárány Society and the International Headache Society to allocate patients to a subgroup: VM, possible VM, and atypical VM. Main Outcome Measure The prevalence of VM, percentages of associated neurotological symptoms, and percentages of effectiveness of prophylactic medication. Results Sixty-five (16%) patients were selected from the total patient population (n = 407) from which 4.2% were assigned to the definite VM group, 5.7% to the probable VM group, and 6.1% to the atypical VM group. We found a significantly different distribution between the groups for photophobia (p = 0.035), ear pressure (p = 0.023), and scotoma (p = 0.015). Thirty patients were administered with flunarizine and 68% responded with an improvement in VM symptoms (p < 0.001). For propranolol, 31 patients were treated and there was an improvement of symptoms in 73% (p < 0.001). Remarkable was the fact that these percentages were not significantly different between the subgroups. Conclusion VM is a common disorder presenting in a dizziness clinic, and detailed history taking is important to assess VM-associated symptoms and thus to prevent underdiagnosis. The latter is very important because our study shows that the majority of patients, regardless of VM subtype, can benefit from a prophylactic treatment, but further prospective studies are necessary.